Do spillovers matter in estimation of private returns to R&D? - Markus Eberhardt; Christian Helmers; Hubert Strauss (European Investment Bank (EIB), 2010)
A large body of literature on the estimation of private returns to R&D adopts the Griliches knowledge production framework, ignoring the impact omitted spillover eects may have on consistent estimation. A separate body of literature is primarily interested in the presence and magnitude of spillovers but imposes a rigid ad hoc structure on the channels these can take, e.g. within-industry, within-country or determined by industry input-output matrices. In this paper we adopt a common factor approach which accounts for R&D spillovers without imposing any arbitrary structure on their nature and channels. At the same time we can account for other unobserved common processes which may affect countries or sectors differentially, e.g. economic shocks or business cycles, as well as heterogeneous evolution of TFP over time.
Keywords: C23; D24; L16; 330; Productivity; R&D; Spillovers; Common Factor Model